Banking Crises under a Central Bank Digital Currency (CBDC) - Lea Bitter (ZBW - Leibniz Information Centre for Economics, 2020)
One of the main concerns when considering Central Bank Digital Currency (CBDC) is the disintermediating effect on the banking sector in normal times, and even more the risk of a bank run in times of crisis. This paper extends the bank run model of Gertler and Kiyotaki (2015) by analyzing the impact of a CBDC. A CBDC is an additional type of liability to the central bank which, by accounting identity, must be accompanied by respective accommodations on the asset side. The model compares the effects of two different asset side policies with each other and to the economy without a CBDC. I find that a CBDC reduces net worth in the banking sector in normal times but mitigates the risk of a bank run in times of crisis. The prevailing concerns about the risk of a bank run turn out to be partial equilibrium considerations disregarding the asset side effects of a CBDC.
Keywords: E42; E58; G01; G21; 330; Central Bank Digital Currency (CBDC); Digital Currency; Central Banking; Financial Intermediation; Bank Runs; Lender of Last Resort